The relationship between school performance and anxiety in adolescents - Sandu, Mihaela; Călin, Mariana Floricica; Segărceanu (Împăratu), Roxana Aurelia (Technium Social Sciences Journal, 2021)
In this paper we analyzed the relationship between school performance and anxiety in adolescents. School performance is closely related to Education and competition, which are two components found in all cultures of the world. The foundations of competition are difficult to identify compared to those of education that are hidden in an unknown past. People have always considered competition and education as important aspects, both in the past and in the present. Educational competitions are found in Romania, as being organized in the form of Olympics and school competitions. These are carried out in accordance with the provisions of the National Education Law no. 1/2011, subsequently completed by the Methodology - framework for conducting and organizing school competitions and is addressed to students in middle and high school classes, being organized by subject, and have as general objective "stimulating students with high school performance or who have interest and special skills in the scientific, technical-applied, cultural-artistic, civic and sports fields ”(MEN, 2011). Subsidiary to this objective we find as mentioned some secondary ones such as the desire to stimulate critical thinking and creativity through the opportunity to manifest motivation in learning and identifying the talents, abilities and knowledge of students of all ages. In Romania, through competitions, the state offers the winners cash prizes, scholarships or places in camps.